HOLISTIC ADAB LEARNING: MODEL PENDIDIKAN ISLAM DI MI ALAM ISLAMIC CENTER PONOROGO - Rahtomo, Hasto; Happy Susanto; Bambang Harmanto (LPPM STAI Muhammadiyah Probolinggo, 2023)
This study aims to describe the implementation of adab learning at MI Alam Islamic Center Ponorogo, focusing on planning, implementation, and evaluation. The research employed a qualitative case study approach with data collected through interviews, observations, and documentation. Data analysis was conducted using Miles & Huberman’s interactive model. The findings reveal that adab learning at MI AIC is designed holistically by integrating Qur’anic values into the curriculum, applying contextual learning methods, and emphasizing teachers’ role modeling. The implementation highlights direct practice, habituation, and school-family collaboration. Evaluation is carried out through behavioral observation, homeroom teacher reports, and parenting forums. The “Holistic Adab Learning” model contributes to Islamic education by presenting an integrative and continuous system of adab learning between school and home. The study implies the importance of school-family synergy in character education based on adab. However, challenges remain, particularly the inconsistency of student behavior between school and home and the limited parental support in maintaining habitual practices.